THE ROLE OF LAW IN OVERCOMING DISCRIMINATION AGAINST MINORITY GROUPS IN THE SOCIAL ENVIRONMENT - Tanti Nurmala Sari (LEX SOCIETAS: Journal of Law and Public Administration, 2025)
Discrimination against minority groups is a complex social problem in Indonesia.This study analyzes the role of law in protecting the rights of minority groups and overcoming discrimination. With a juridical-normative approach and case studies, this study finds that law is effective as a tool to regulate, protect and punish discrimination.The Human Rights Law and the Discrimination Eradication Regulation are strategic legal bases. Increasing public legal awareness and consistent implementation are urgently needed. Discrimination against minority groups is still a deep social problem in Indonesia. Law has a strategic role in overcoming this discrimination. This study aims to analyze the role of law in protecting the rights of minority groups and overcoming discrimination. The research method uses a juridical-normative approach and case studies. The results of the study show that law can act as a tool to regulate, protect and punish discrimination. Law No. 40 of 1999 concerning Human Rights and Government Regulation No. 57 of 2021 concerning the Eradication of Discrimination are effective legal bases. However, it is still necessary to increase public legal awareness and consistent implementation of the law